Practical torque tracking control of electro-hydraulic load simulator using singular perturbation theory. (July 2020) - Jing, Chenghu; Xu, Hongguang; Jiang, Jihai
Abstract: Nonlinear and high-order characteristics could directly hinder the application of many advanced control algorithms for electro-hydraulic system which is a coupling system with double-dynamics of mechanical and hydraulic components. In this paper, a practical torque tracking control using singular perturbation theory is proposed for electro-hydraulic load simulator. The system model is transformed into a singularly perturbed form including a slow mechanical system and a fast hydraulic system. To achieve high accuracy and strong robustness, an active disturbance rejection control based on desired model compensation is developed for the slow mechanical system. It is proved that the mechanical system with developed slow controller is exponentially stable. A proportional control law is employed for the fast hydraulic system. This hydraulic system with developed fast controller is demonstrated to be exponentially stable. Stability of the whole closed-loop system is theoretically analyzed using the extended Tikhonov's theorem. Experimental results validate the presented control scheme. Highlights: Electro-hydraulic system is formulated into a singularly perturbed form. A novel error based active disturbance rejection control is designed for a slow mechanical system. A proportional control law is used for a fast hydraulic system. The mechanical system and hydraulic system are asymptotically stable. The stability is analyzed using the extended Tikhonov's theorem.